Soybean shows an attenuated nitrogen dilution curve irrespective of maturity group and sowing date - Divito, Guillermo Adrián (2016)
It is generally accepted that the nitrogen (N) dilution curves relating shoot nitrogen concentration (%N) and shoot biomass (W) are similar among genotypes from the same species. However, differences in the pattern of biomass ratio between lamina and stem (Wlam:Wste) with increasing biomass would change the curve. Shoot biomass at flowering also affect biomass and N allocation in legumes and would affects the N dilution. In soybean, maturity groups (MG) or sowing dates can lead to differences in Wlam:Wste and in time from sown to flowering and hence the parameters of N dilution curves could be affected. The aims of this study were: (i) to determine the growth and allocation patterns of soybean as affected by maturity group (MG IV vs II) and sowing date and (ii) to establish allometric relations between growth and nitrogen, including N dilution curves. Our working hypothesis is that the reference N dilution curve in soybean is similar to the critical N dilution curve of non-legume C3 crops. Four experiments were performed at Balcarce, Argentina during three growing seasons with the aim to generate a wide range of growing conditions. Two soybean cultivars were evaluated: DM2200 (MG II) and DM4970 (MG IV), sown in optimum dates for the region (mid-November). DM2200 was also sown late (early January). We sampled crops between W ≈ 1 Mg ha−1 and R5. Shoots were separated in three compartments: lamina (Wlam), stem and petiole (Wste) and pod (Wpod). Despite the marked decrease in Wlam:Wste with increasing biomass, the N dilution curve was attenuated in soybean, with no differences among cultivars of maturity groups II and IV, and sowing dates from November to January. We propose that early pod onset and the constant%N in lamina and stem between R1 and R5 attenuated the N dilution curve in all MG and sowing date. Timely-sown MGIV showed a greater Wlam:Wste ratio at W = 1 Mg ha−1 and a more pronounced depletion of the ratio with increasing biomass. However, the N dilution curves were similar between maturity groups II and IV, and sowing dates from November to January. This could be attributed to the lower%N in lamina at V6 in comparison to R1 in timely-sown MGIV.